The Orthopedic Diseases of Ancient Egypt. Issue 6 (June 2015) - Fritsch, Klaus O; Hamoud, Heshem; Allam, Adel H.; Grossmann, Alexander; Nur El‐Din, Abdel‐Halim; Abdel‐Maksoud, Gomaa; Al‐Tohamy Soliman, Muhammad; Badr, Ibrahim; Sutherland, James D; Linda Sutherland, M.; Akl, Mahmoud; Finch, Caleb E; et al.
ABSTRACT Background: CT scanning of ancient human remains has the potential to provide insights into health and diseases. While Egyptian mummies have undergone CT scans in prior studies, a systematic survey of the orthopedic conditions afflicting a group of these ancient individuals has never been carried out. Methods: We performed whole body CT scanning on 52 ancient Egyptian mummies using technique comparable to that of medical imaging. All of the large joints and the spine were systematically examined and osteoarthritic (OA) changes were scored 0‐4 using Kellgren and Lawrence classification. Results: The cruciate ligaments and menisci could be identified frequently. There were much more frequent OA changes in the spine (25 mummies) than in the large joints (15 cases of acromioclavicular and/or glenohumeral joint OA changes, five involvement of the ankle, one in the elbow, four in the knee, and one in the hip). There were six cases of scoliosis. Individual mummies had the following conditions: juvenile aseptic necrosis of the hip (Perthes disease), stage 4 osteochondritis dissecans of the knee, vertebral compression fracture, lateral patella‐femoral joint hyper‐compression syndrome, severe rotator cuff arthropathy, rotator cuff impingement, hip pincer impingement, and combined fracture of the greater trochantor and vertebral bodies indicating obvious traumatic injury. This report includes the most ancient discovery of several of these syndromes. Conclusions: Ancient Egyptians often suffered painful orthopedic conditions. The high frequency of scoliosis merits further study. The pattern of degenerative changes in the spine and joints may offer insights into activity levels of these people. Anat Rec, 298:1036–1046, 2015. © 2015 Wiley Periodicals, Inc.